Особливості нарахування та списання торгoвої націнки на підприємствах ресторанного господарства - Бегун, Світлана Іванівна; Ворона, Ольга А.; Begun, Svitlana I.; Vorona, Olha A. (Луцький національний технічний університет, 2014)
У статті розглянуто особливості нарахування та списання торговельної націнки на підприємствах ресторанного господарства, наведені підходи до встановлення продажної ціни продукції. Recently conduct restaurants become more popularity. A restaurant is a business which prepares and serves food and drink to customers in return for money, either paid before the meal, after the meal, or with an open account. The successful operation of the restaurant, café and bars depends largely on accounting. In the conduct of accounting in the restaurant industry, special attention should be paid to the account of trade margin. The article deals with the features of charges and write-offs of trade margins on the restaurants and catering enterprises. Before the company independently chooses on which accounting price (buying or selling) is accounting for goods and products. In practice, there are two approaches to setting the selling price of products and determination of margins. First, a direct method is determined based on expenditures and expected profits. Second, the inverse calculation, according to which, a fixed price, retail margin and the amount of VAT calculated inverse method. As for writing off trade margin, it is written off by the method of "reverse". However, questions remain about unresolved the informative apparatus, there is lack of method of accounting trade margin for restaurants and catering enterprises, and therefore restaurants institution has sole discretion to choose the method of trade margin.
Features of charges and writing off the retail margin in the restaurnt business enterprise
Keywords: підприємство ресторанного господарства; роздрібні ціни; торгова націнка; ціна реалізації; списання торговельної націнки; метод сторно; the restaurant business enterprise; the retail price; the retail margin; the selling price; writing off the retail margin; the reversal method